Filter Bubble Phenomenon on Instagram and Its Impact on Teenagers Lifestyle and Social Interaction - Misnawati, Desy; Perdana, Bosya; Ariana, Sunda; Damayanti, Novita; Saputra, Dhimas Rosanto (Pandawan, 2025)
This research aims to analyze the phenomenon filter bubble on Instagram and its impact on lifestyle changes and social interactions of teenagers aged 16-20 years in Palembang. Instagram, as a visual-based social media platform, uses Artificial Intelligence (AI) algorithms to customize and filter content according to user preferences, which can influence user thought patterns, attitudes and behavior. In this research, a qualitative approach was used with literature study methods and content analysis. Data was collected through in-depth interviews with teenagers in Palembang who actively use Instagram. The research results show that filter bubble influencing teenagers in adopting lifestyle trends, especially in terms of appearance and beauty, such as the use of makeup which often appears in Instagram feeds. In addition, this phenomenon also contributes to the formation of homogeneous social groups, where teenagers are more likely to interact with individuals who have similar interests, while different views tend to be ignored. Based on Information Integration Theory, this research explains that information received via social media, which is filtered by the Instagram algorithm, shapes teenagers attitudes and behavior. The conclusion of this research is that the phenomenon filter bubble has a significant impact on the development of teenagers lifestyles and social interactions, which has the potential to narrow their horizons to various perspectives. Therefore, better digital literacy is needed to help teenagers be more critical in consuming information on social media.